Performance Comparison of API Protocols: A Systematic Review of REST, GRPC and Graph QL (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The correct choice of API protocols in the modern distributed systems defines the level of performance, scalability, and resource efficiency. The current paper contains a systematic literature review (SLR) of 20 empirical studies in total published in 2020-2025 by comparing the top three architectural styles, namely, REST, gRPC, and GraphQL. This review offers a review of the evidence-based framework of protocol selection by synthesizing data on latency, throughput, resource utilization, and scalability.Our results suggest that gRPC provides the shortest latency with small message payloads since it uses HTTP/2 multiplexing and Protobuf serialization, thus this is best suited to inter-service communication. REST has the best raw throughput (1500-2000 RPS on average) but it has head-of-line blocking, and data over-fetching. On the other hand, GraphQL reduces memory usage (around 17 percent versus 20 percent with REST/gRPC) due to accurate field selection, but has high CPU cost in query parsing and resolution.The review has been found to have significant research gaps, the most notable of which is absence of standardized three way benchmarking and performance analysis of the production scales. This paper ends with evidence-based suggestions of hybrid architecture solutions to provide an architectural and research base of selecting approaches to microservices in architectural projects.